Using PLS-SEM algorithm for Choice of University in Vietnam - Ngan, Nguyen Thi; Khoi, Bui Huy (Journal of physics. Conference series, 2021)
The paper tested the factors which influenced the choice of university. Survey data were gathered from 318 students studying at Ho Chi Minh City Industrial University, Vietnam. In the sense of education in Vietnam, the study model was suggested from the university choice studies. We used the PLS-SEM algorithm in Adanco software for analyzing statistics. PLS-SEM algorithm shows that university choice (LC) has been influenced by the University Choice’s five components including Future career expectation (DU), University Reputation, Enroll opportunity (CH), Individual capacity (NL), and Group references (NTK). University Characteristics (DD) and Communication (TT) at university were not influenced University Choice of Student.